PROBLEMATIKA PENGELOLAAN ASET BUKU DI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Annisa, Dea; Hidayat, Endik (Jurnal Progress Administrasi Publik, 2024)
To realize the intelligence of the Indonesian nation as stated in the 1945 Constitution, the role of libraries is needed, which has been regulated in Law No. 43 of 2007 which discusses libraries. The library serves as a means of education, preservation, recreation, research, and information to improve the quality of intelligence and empowerment of the nation. So is the East Java Provincial Library and Archives Office, of course, there are things to be achieved in its goal of educating the nation with a library collection sourced from the receipt of library materials. This acceptance comes from the purchase of books every year. These are managed by the Deposit, Development, and Preservation of Library Materials in the Development sub-field. These are also adjusted to the National Library Standards. This will be related to Warwick's theory (1979) regarding policy implementation with four elements, namely organizational capability, information, support, and potential sharing. What must be adjusted for the implementation of a policy. The research used a descriptive qualitative method using a descriptive approach with observation, interviews, and documentation. The results of this study are that there are problems related to human resources and existing facilities, although in the process of receiving, namely purchasing books, it can be said that it runs smoothly, but in the management process there are various obstacles starting from the lack of human resources and also available facilities. Therefore, it can be said that the implementation of this policy has not been maximally implemented.   Keywords: Implementation; Policy; Library